Professional Development That Positions Teachers as Inquirers and Possibilizers (LEARNing Landscapes, 2015)
What might braiding social justice orientations to teaching, learning, and educational change with collaborative inquiry-based professional development afford teachers, their students, and our communities? This article unpacks two professional development initiatives to articulate how inquiry co-constructed by and with teachers can take up diversity as generative. The Aboriginal Early Literacy and Curriculum for All projects involved iterative and critical examinations of practice and opportunities for educators to collaboratively consider and create practices that address contextual and social factors. Educators worked together to situate emerging knowledge and beliefs while also challenging the sources and consequences of assumptions.
Keywords: professional development; practice; social justice; diversity; collaboration; teacher; inquiry